Studi Literatur: Analisis Implementasi Keamanan Aset Informasi Dalam Mendukung Pengembangan UMKM di Indonesia - irvan, Irvan Satya Nugraha; Muhammad Randa Syuhada; Muhammad Rifai Harahap; Aninda Muliani Harahap (Jurnal Ekonomi dan Keuangan Syariah, 2022)
The presence of Information Technology (IT) has changed the way of business by providing new opportunities and challenges that are different from conventional ways. The information system implemented in UMKM activities deserves to be protected. The developed information system is a model for small and medium enterprises. This study aims to investigate the implementation of information asset security in UMKM and the challenges it will face in the future. This study uses a qualitative method with a literature study approach. This research was assisted by the www.researchgate.net web application to collect relevant data and then conduct content analysis. The sample used in this study is journal papers that are relevant to the topic of national UMKM and information asset security during the COVID-19 period in the 2020-2022. The results of this study indicate that some UMKM have implemented an information asset security system in their operational activities, while some other UMKM still operate traditionally manually without involving information technology. The challenge ahead is the problem of increasing the knowledge, awareness and caution of operators to avoid data input errors as well as periodically checking the security of the security system. It is hoped that the collaboration of government, academics and UMKM practitioners can help answer these challenges